Governing the Responsible Pilgrim: Da’wah, Surveillance, and Islamic Governmentality in the Prevention of Illegal Hajj - Zain, Machsun; Aswadi; Fuad, Ahmad Nur (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the mechanisms for preventing illegal hajj pilgrimages at the Ministry of Religious Affairs Regional Office in East Java through a Foucauldian governmentality framework. Using a qualitative case study methodology, data were collected through in-depth interviews with 15 ministry officials, direct observation of regulatory practices over 6 months, and documentary analysis of ministerial regulations, standard operating procedures, and enforcement records from 2023 to 2025. Data were systematically coded to identify governmental rationalities (e.g., risk management, spiritual welfare protection), technologies of power (e.g., registration databases, site inspections), and subject positions (e.g.,